2020
DOI: 10.1051/0004-6361/202038504
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the magnetar XTE J1810−197 at 150 and 260 GHz with the NIKA2 kinetic inductance detector camera

Abstract: Context. The investigation of pulsars between millimetre and optical wavelengths is challenging due to the faintness of the pulsar signals and the relative low sensitivity of the available facilities compared to 100 m class telescopes operating in the centimetre band. The kinetic inductance detector (KID) technology offers large instantaneous bandwidths and a high sensitivity that can help to increase the ability of existing observatories at short wavelengths substantially to detect pulsars and transient emiss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
2
16
1
Order By: Relevance
“…High-frequency radio emission is a hallmark feature of radio magnetars. Bright radio pulses have been detected from several radio magnetars in the Milky Way at record high frequencies, well above 100 GHz in some cases(e.g., see Camilo et al 2007;Torne et al 2017Torne et al , 2020, but no FRBsource has yet been detected at radio frequencies above 8 GHz. However, to date, very few searches for FRBs have been carried out at such high radio frequencies (Gajjar et al 2018;Majid et al 2020).…”
Section: Progenitor Modelsmentioning
confidence: 99%
“…High-frequency radio emission is a hallmark feature of radio magnetars. Bright radio pulses have been detected from several radio magnetars in the Milky Way at record high frequencies, well above 100 GHz in some cases(e.g., see Camilo et al 2007;Torne et al 2017Torne et al , 2020, but no FRBsource has yet been detected at radio frequencies above 8 GHz. However, to date, very few searches for FRBs have been carried out at such high radio frequencies (Gajjar et al 2018;Majid et al 2020).…”
Section: Progenitor Modelsmentioning
confidence: 99%
“…Kramer et al 2003). The flatness of the radio spectrum has led to the detection of radio-loud magnetars up to a frequency of ∼300 GHz (Torne et al 2017(Torne et al , 2020, which is the highest radio frequency of any neutron star detection so far.…”
Section: Introductionmentioning
confidence: 99%
“…The time gaps between observations are smaller than 24 hours if not simultaneous. Figure 5 shows five spectra between December 2018 and April 2019, with early results of precedent studies (Maan et al 2019;Dai et al 2019;Pearlman et al 2019Pearlman et al , 2020Torne et al 2020). Our upper limit at 0.3 GHz is marked as well.…”
Section: Spectral Variationsmentioning
confidence: 55%
“…Gotthelf et al (2019) reported an earlier increase of its Xray flux between MJDs 58442 and 58448, and confirmed X-ray outburst has preceded the radio burst. Many radio follow-up observations have reported the broad frequency range of its radio activity during this outburst, from 300 MHz (Maan et al 2019) to a few GHz (Levin et al 2019;Dai et al 2019;Johnston et al 2020), to 32 GHz (Pearlman et al 2019) and even up to 150 GHz and 260 GHz (Torne et al 2020).…”
Section: Introductionmentioning
confidence: 92%